Examining the relationship between academic stress and motivation toward physical education within a semester: A two-wave study with Chinese secondary school students - Yang, Menglu; Viladrich, Carme; Cruz, Jaume (Frontiers in Psychology, 2022)
The present study aimed to investigate the relationship between academic stress and motivation toward physical education (PE) through a longitudinal design with cross-lagged panel analyses. A sample of 556 Chinese secondary school students participated in the research and completed Perceived Locus of Causality Scale and Educational Stress Scale for Adolescents at the beginning of the semester and 3 months later. The results demonstrated that academic stress factors were positively related to less self-determined motivations except that worry about grades was positively related to more self-determined motivations within each time point. In addition, we found that academic stress negatively predicted more self-determined motivations but positively predicted less self-determined motivations, whereas worry about grades negatively predicted amotivation 3 months later. Meanwhile, the influence of amotivation on despondency was also found. These results suggest that academic stress can obstruct students’ participation in PE through an impact on self-determined motivation. Our findings also indicate that self-determined students in PE will seek academic achievement as well, which in turn improves students’ academic status.